2006
DOI: 10.1001/archneur.63.6.851
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis Optica in Patients With Myasthenia Gravis Who Underwent Thymectomy

Abstract: Background: Myasthenia gravis (MG) and neuromyelitis optica (NMO, also known as Devic disease) are rare autoimmune disorders, with upper-limit prevalence estimates in the general population of 15 per 100 000 and 5 per 100 000, respectively. To our knowledge, an association between these diseases has not been previously reported. Objectives: To describe 4 patients with MG who developed NMO after thymectomy and to analyze possible causes of apparent increased prevalence of NMO among patients with MG. Design: Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 41 publications
3
51
0
4
Order By: Relevance
“…This patient resembles those reported by Kister et al 9 , who suggested that unspecific immune dysregulation, either due to thymectomy or genetic susceptibility might influence the development of a second autoimmune disease. Although all our patients achieved a good control of myasthenia symptoms, we could not determine the influence of developing dd on MG control due to the small number of patients in this series.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This patient resembles those reported by Kister et al 9 , who suggested that unspecific immune dysregulation, either due to thymectomy or genetic susceptibility might influence the development of a second autoimmune disease. Although all our patients achieved a good control of myasthenia symptoms, we could not determine the influence of developing dd on MG control due to the small number of patients in this series.…”
Section: Discussionsupporting
confidence: 89%
“…The occurrence of dd in association to MG have been reported before, and are described as monophasic events (myelitis, acute disseminated encephalomyelitis and optic neuritis) [10][11][12][13] and recurrent diseases (multiple sclerosis, recurrent transverse myelitis and NMo) 7,[9][10][11][12]14 . some authors state that this association may not happen by chance, as the incidence of dd in patients with MG is much higher than expected in the general population 6,15 , and both may be part of multiple autoimmune syndromes or genetic predisposition to autoimmunity 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that these 8 8 patients have two coexisting autoimmune disorders rather than a vasculitic complication of a systemic autoimmune disease such as SLE or SS (35,36). Similarly, NMO may coexist with myasthenia gravis or other systemic autoimmune diseases (37,38) (Fig 8).…”
Section: Inflammatory Myelopathiesmentioning
confidence: 99%